YOUNG PEOPLE UP TO 24 YEARS ON THE LABOUR MARKET IN A SMALL SLOVAK TOWN - Markovič, Daniel; Tomlák, Viktor; Šrobárová, Soňa; Gejdošová, Zuzana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Social pedagogy offers a wide multidisciplinary range to prevent and tackle youth unemployment. In this paper, we want to broaden the knowledge for social pedagogues in the areas of young people in the labour market and youth unemployment. The aim of the research is to identify the experience of respondents in the labour market in the district of Ruzomberok. It is a district in Slovakia far from the capital and regional centres. Most of the district´s inhabitants live in villages, fewer inhabitants in a town of Ružomberok. We conducted a questionnaire survey of 100 respondents. There are 50 young people up to 24 years old, who are currently active in the labour market. Furthermore, there are persons unemployed, registered at the Office of Labour, Social Affairs and Family in Ružomberok, with an age limit of up to 24 years, representing the same number of 50 respondents. We explored the social context; we set two hypotheses: There is a statistically significant difference in the status of the labour market with respect to the respondents' residence. There is a statistically significant difference in the status of the labour market relative to the gender of respondents. To verify the hypotheses, we used the Chi-Square-2 variable test. The hypotheses were not confirmed.